Nomenclatural notes in the Pleurothallidinae (Orchidaceae): miscellaneous - Karremans Lok, Adam Philip (2019)
Nomenclatural amendments and notes are provided for taxa belonging to diverse genera within subtribe Pleurothallidinae (Orchidaceae) in order to comply with the International Code for algae, fungi, and plants. The proposed changes include new species, new names, new combinations, author citations, name spelling and synonymy. Brief notes are provided.